Impact of perceived value on intention to use voice assistants: the moderating effects of personal innovativeness and experience. - Molinillo-Jiménez, Sebastián; Rejón-Guardia, Francisco; Anaya-Sánchez, Rafael; Liébana Cabanillas, Francisco (Wiley, 2023)
Voice assistants (VAs), such as Alexa, Siri and Google Assistant, are instruments increasingly used by consumers to perform daily tasks. The objectives of the present study are to examine the antecedents of consumers’ continuance intention to use VAs and the moderating effects of personal innovativeness and experience. Based on behavioral reasoning theory, a research model is proposed to provide insights into the drivers of continuance intention to use. Two empirical studies, based on data collected via online surveys, were conducted. The model was analyzed through partial least squares structural equation modeling. The findings of the studies showed that emotional value and performance expectancy were key antecedents of continuance intention to use, which in turn positively influenced actual use and word-of-mouth intention. In contrast, quality value was a significant antecedent of continuance intention to use in only one of the two studies, and the influence of price value, social value, effort expectancy and privacy risk were not found to be significant. However, the second study showed that several of these relationships are moderated by the consumer’s experience and personal innovativeness; specifically, less innovative users are sensitive to quality value and experienced users are sensitive to social value.
Keywords: Inteligencia artificial; Artificial intelligence; Voice assistant; Smart speaker; Consumer bahavior; Perceived value; Continuance intention to use; Experience; Innovativeness